Enhancing Human Security by Transforming Education Through Science, Technology, and Innovations - Jon-Hans Coetzer; Lucía Morales & Patrick Flynn; Lia Pop, Nadia Barkoczi, Sonia Munteanu & Cristina Campian; Daniel Rajmil (Cadmus, 2023)
In this paper, we provide in-depth critical analysis and reflections on how technology, innovation and digital literacy can help to bring awareness on the need for a new dimension and approach to foster a transformational attitude towards education. Learning drives change, and if we aim to make an impact, there is a need to enable collaboration between different disciplines so that new transformative educational models can emerge. At the centre of our analysis, we identify the role of pedagogy and how it can contribute to put forward humans as central and critical actors in using science, technology, and innovations (STIs) to foster human security. We explore the critical role of Higher Education Institutions (HEIs) and their engagement with science, technology, and innovation in the search for educational transformation that supports multicultural, diverse and inclusive learning environments within the tenets of social engagement and cohesion that guide us towards the principles of human security.